THE EFFECT OF INTERNAL PUBLIC RELATIONS CAMPAIGN PROGRAMME TOWARDS EMPLOYEES BEHAVIORAL CHANGES - Lestari, Ruth Esther Ken; Hartanti, Lisa Esti Puji (School of Communication - Atma Jaya Catholic University of Indonesia, 2018)
Nowadays, environmental crisis becomes our challenge. Therefore, we must take care of our environmental problems together. Atma Jaya Catholic University of Indonesia as one of the educational institutions in Indonesia also contributes to take care of our environmental problems through an environmental awareness campaign program named #CerMatKerLAP (Saving Papers, Electricity, Water, and Plastics Smartly). The main purpose of this research is to understand the effect of the program towards Atma Jaya’s employee behavioral changes. Then, publication is needed to support the internal public relations campaign program, also as the communications tools, so the messages will be well delivered to the public. The theories used by this research are the types of publication based on the internal public relations campaign (printed materials, spoken & visual words, media gathering) and the five steps of behavioral changes by Everett Rogers (Awareness, Interest, Evaluation, Trial, Adaptation – AIETA Model). The method used by this research is quantitative with questionnaire as the data collection method. The sampling technique used by this research is stratified sampling with Atma Jaya’s permanent employees who know the campaign as the respondents of this research. The sample obtained for this research are 90 respondents. The result shows that the #CerMatKerLAP internal public relations campaign affects positively and significantly contributes to the behavioral changes of Atma Jaya’s permanent employees.